2015
DOI: 10.1051/0004-6361/201526504
|View full text |Cite
|
Sign up to set email alerts
|

Probing the final stages of protoplanetary disk evolution with ALMA

Abstract: Context. The evolution of a circumstellar disk from its gas-rich protoplanetary stage to its gas-poor debris stage is not understood well. It is apparent that disk clearing progresses from the inside-out on a short time scale and models of photoevaporation are frequently used to explain this. However, the photoevaporation rates predicted by recent models differ by up to two orders of magnitude, resulting in uncertain time scales for the final stages of disk clearing. Aims. Photoevaporation theories predict tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
55
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 97 publications
(121 reference statements)
5
55
2
Order By: Relevance
“…In the inner disk (∼ 1AU), however, there appears to be clearer evidence of simultaneous dispersal. The fraction of accreting disks (withṀ acc > 10 −11 M ⊙ yr −1 ) in stellar groups declines on timescales similar to those of NIR excesses (Fedele et al 2010), with some non-accreting sources (withṀ acc < 10 −11 M ⊙ yr −1 ) still showing IR excesses (also Ingleby et al 2013, Hardy et al 2015. This may indicate that gas in the inner disk is removed first, consistent with dispersal scenarios (see Alexander et al 2014).…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…In the inner disk (∼ 1AU), however, there appears to be clearer evidence of simultaneous dispersal. The fraction of accreting disks (withṀ acc > 10 −11 M ⊙ yr −1 ) in stellar groups declines on timescales similar to those of NIR excesses (Fedele et al 2010), with some non-accreting sources (withṀ acc < 10 −11 M ⊙ yr −1 ) still showing IR excesses (also Ingleby et al 2013, Hardy et al 2015. This may indicate that gas in the inner disk is removed first, consistent with dispersal scenarios (see Alexander et al 2014).…”
mentioning
confidence: 62%
“…Sub-millimeter emission is rarely seen from disks without NIR excesses (Andrews & Williams 2005), indicating either that the entire disk is depleted simultaneously or that the larger grains are lost earlier due to some combination of drift, fragmentation and/or planetesimal formation. Dust at mid-infrared wavelengths appears to last slightly longer (e.g., Wahhaj et al 2010, Hardy et al 2015; see Figure 1), however, debris disks may contaminate emission statistics at these wavelengths. Nevertheless, the transition from optically thick to optically thin disksbelieved to be represented by a class of objects called transition disks-appears to proceed from inside-out, .i.e., the inner dust is depleted first.…”
mentioning
confidence: 99%
“…Based on a lack of CI emission toward the disk around CQ Tau, Chapillon et al (2010) concluded that the weak CO emission previously observed for this disk is due to depletion of the gas as a whole, not just of CO. Focusing on disks later in their evolution, Hardy et al (2015) observe 24 sources with ALMA lacking signs of ongoing accretion, but still showing infrared excesses indicative of dust. While four of these sources are detected in the 1.3 mm continuum, none are detected in 12 CO J=2-1.…”
Section: The Relationship Between Gas and Dustmentioning
confidence: 99%
“…Several sources are in the 10 Myr regime. At such ages, many systems already show low emission levels consistent with debris disks (e.g., Hardy et al 2015;Wyatt et al 2015). This is particularly surprising since A stars are thought to lose their disks faster (Ribas et al 2015) and suggests that the giant planet systems responsible for clearing large portions of the inner disk may contribute to disk longevity by trapping material in the outer disk.…”
Section: The Longevity Of B a F Star Disksmentioning
confidence: 99%